Application of digital signal processing in radar : a study - Ab Ghani, Mohd Sabri; Hashim, Nik Mohd Zarifie; Abdullah Zawawi, Noor Liliah Erlina; Darsono, Abd Majid; Salleh, Azahari; Mohamad, Najmiah Radiah (IJAERT, 2014)
Nowadays, most of the electronic devices used Digital Signal Processing (DSP). This paper discussed the block diagram, radar detection, implementation of a convolution, Doppler processing, scanning, compression and filtering that been used in the applications of DSP in Radar purposes.